The impact of forest management plans on trees and carbon: Modeling a decade of harvesting data in Cameroon - Cerutti, P.O.; Suryadarma, D.; Nasi, Robert; Forni, E.; Medjibe, V.P.; Delion, S.; Bastin, D. (Elsevier, 2017)
By 2010, about 25% (180millionha) of The International Tropical Timber Organization (ITTO) producer countries’ permanent forest estate was being managed using an approved forest management plan (FMP). While the existence of a FMP is often used as evidence of sustainable forest management (SFM), State officials mandated to monitor and verify FMPs’ implementation often lack the technical knowledge and political incentives to assess the changes that have been introduced, notably in terms of harvested volumes and species. Among tropical timber producers, Cameroon is considered to be exemplary for its progressive forest regulatory framework. Here we aim to estimate for the first time in sub-Saharan Africa the causal impact of the implementation of FMPs on harvested volumes, species and carbon stocks. We do so by using a 12-year (1998–2009) unbalanced longitudinal data set of a detailed, official harvesting inventory of 81 concessions in Cameroon. Results provide evidence to the theoretical expectations that for many years many practitioners have had on the implementation of SFM, i.e. that FMPs show a substantial opportunity to reduce carbon emissions from forest while presenting logging companies with acceptable financial trade-offs. We explore the technical and political reasons for our findings and conclude that these analyses are important for countries that are underwriting carbon-related schemes in which they propose to reduce their emissions through the effective implementation of SFM. We also demonstrate that producer countries do record useful information that, when effectively used, can help them to inform their policies and improve their sustainable development strategies.